THE INDIVIDUAL CHARACTERISTICS OF ADOLESCENTS BEING AT RISK OF INTERNET ADDICTION - Kiseleva, T.G.; Enzeldt , N. V.; Shmakov , I. A. (Modern Psychology, 2019)
The Internet is an important part of the teenagers’ life and source of the problem. One of them is an Internet addiction. In the article authors analyze the existing approaches to the study of the Internet addiction phenomenon, types, factors and stages of Internet addiction formation, as well as the motivation of Internet-addicted behavior. In the course of empirical research authors have defined some factors, formed the basis of the study of adolescent behavior. More than half of the survivors have a moderate or high susceptibility to Internet addiction, and the dominant symptoms in these adolescents are a violation of the communications, the avoidance of problems and responsibilities, self-dependence and anonymity as a special value. According to the study authors have made recommendations on the organization of socio-psychological and social-pedagogical work in prevention of Internet addiction in adolescents.
Keywords: Internet addiction; adolescents; impaired communication; avoidance of responsibility; independence and anonymity as a value